ESTIMATION OF THE USEFULNESS OF GLASSY CARBON ELECTRODE IN NON-AQUEOUS SOLVENTS POLARIZED TO HIGHER ANODIC POTENTIALS - KISS, László; KUNSÁGI-MÁTÉ, Sándor (Studia Universitatis Babeș-Bolyai Chemia, 2020)
In this paper, suitability of glassy carbon electrode in numerous non-aqueous solvents used widely in electrochemistry (methanol, acetone, dichloromethane, nitrobenzene, nitromethane, 1-butanol, dimethyl sulfoxide, dimethyl formamide, tetrahydrofuran) was studied by changing the potential of preanodisation. The potential range studied in viewpoint of preanodisation effect was between 1 and 3 V. At higher potentials, glassy carbon electrode deactivated in many solvents which was clearly demonstrated using the aqueous solution of a redox probe 1,4-dihydroxybenzene. Due to the low permittivity, some solvents (ethyl acetate, chloroform) were investigated using a preanodisation at 3 V because of the significant ohmic drop and the surface state also changed. Results highlight the importance of this limitation caused by polarizing above 2 V and it must be considered when glassy carbon electrode is selected for the investigations carried out in these conditions.